The Dilemmas And Parenting Strategies Of Working Parents In The Digital Age: The Roles And Challenges Of Parents In Raising Children In An Era Of Increasingly Advanced Technology - Damayanti, Karina; Eddyono, Aryo Subarkah (Journal Research of Social Science, Economics, and Management, 2026)
As technology evolves, so do the concerns about children’s dependency on gadgets and the potential behavioral issues, such as aggression, that arise when devices are restricted. This research explores how digital media and technology impact parent-child relationships in the modern age, focusing on how parents manage their children's use of technology. By adopting a qualitative approach, this research examines the phenomenon of Intimate Surveillance, which describes how parents balance monitoring and guiding their children in the digital world with a focus on love and care, rather than authoritarian control. In this era, digital parenting requires a shift from traditional control toward understanding how children form their identities, values, and meaning through interactions in the digital space. The study highlights the complexities faced by parents in navigating the digital landscape, as they seek to maintain a balance between freedom and discipline. The findings emphasize that parents are no longer just authorities but partners in guiding their children’s digital experiences. The concept of Intimate Surveillance shows how parents act as both protectors and facilitators, helping children make responsible decisions in the digital world. The research underscores the importance of open communication, emotional support, and digital literacy as essential components of modern parenting. As children grow and engage more with technology, parents must adapt, ensuring that they foster a healthy, balanced relationship with technology that supports their children’s development while minimizing risks like addiction or exposure to inappropriate content.